A super-lithiophilic nanocrystallization strategy for stable lithium metal anodes. (July 2020) - Feng, Yong-Qiang; Zheng, Zi-Jian; Wang, Cao-Yu; Yin, Ya-Xia; Ye, Huan; Cao, Fei-Fei; Guo, Yu-Guo
Abstract: Regulating the surface morphology or physical properties of current collectors, and thus tuning the wettability of liquefied Li toward substrates, is of tremendous interest for stabilizing Li metal anodes. Here we show the wettability of molten Li toward substrates can be tuned by nonreactive surface nanocrystallization strategy. The nanocrystallization structural features result in a surface energy reduction and generation of Laplace pressure, with both factors acting together to achieve a rapid adsorption of Li. The as-obtained Li composite anode exhibits a stable and low voltage hysteresis of less than 20 mV for over 2000 h at 0.5 mA cm −2 in a symmetrical cell owing to metal nanoseeds in the 3D scaffold. Equipped with the fabricated Li metal anode, a rechargeable Li metal battery with LiFePO4 cathode that features a high areal capacity of over 3 mA h cm −2 and long cycling stability is achieved. This finding provides a facile and cost-effective strategy for stabilizing Li metal for high-energy batteries. Graphical abstract: The rapid wettability of molten Li toward substrates have been realized by the driving force of surface energy reduction and Laplace pressure that originates from surface dispersed nanoparticles. Image 1 Highlights: Rapid wettability of molten Li toward hosts can be obtained by anchoring metal nanoparticles. Uniform Li deposition, low nucleation overpotential, and long lifespan can be achieved. A full cell with an areal capacity of 3 mA h cm −2 show good cycle life. The strategy can be applied to molten Na metal or other metals.